2021
DOI: 10.1111/jace.17975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zirconia content and particle size on the properties of 3D‐printed alumina‐based ceramic cores

Abstract: Ceramics usually have high hardness which is difficult to achieve, especially for complex parts with fine structures. [1][2][3][4] Considering the requirements of ceramic cores with rather intricate structures and requiring high precision, it is essential to develop fast, low cost, and high-precision ceramic-forming techniques. 5,6 Ceramic cores are applied in the form of internal passages for high-temperature hollow blades, a key factor to determine the quality of hollow blades. 7 Traditional preparation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…observed through X‐ray photoelectron spectrometer (XPS) measurements that Fe 2 O 3 additions resulted in a higher ratio of O:Al, suggesting that doping with Fe 2 O 3 increased the surface adsorption of oxygen molecules or atoms and lowered the onset temperature of transformation. Although it is well‐reported that certain cations, such as Ca 2+ , Zr 4+ , Fe 3+ , and Ti 4+ , accelerated structural changes, other cations like Ba 2+ , La 3+ , and Si 4+ delayed them 43,49,50 . Several groups have also suggested that the pH of starting Al(OH) 3 powder suspensions influenced the final particle size and shape, 30 which affected the onset temperature of α‐Al 2 O 3 formation, as well as the transformation sequence leading to α‐Al 2 O 3 51,52 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…observed through X‐ray photoelectron spectrometer (XPS) measurements that Fe 2 O 3 additions resulted in a higher ratio of O:Al, suggesting that doping with Fe 2 O 3 increased the surface adsorption of oxygen molecules or atoms and lowered the onset temperature of transformation. Although it is well‐reported that certain cations, such as Ca 2+ , Zr 4+ , Fe 3+ , and Ti 4+ , accelerated structural changes, other cations like Ba 2+ , La 3+ , and Si 4+ delayed them 43,49,50 . Several groups have also suggested that the pH of starting Al(OH) 3 powder suspensions influenced the final particle size and shape, 30 which affected the onset temperature of α‐Al 2 O 3 formation, as well as the transformation sequence leading to α‐Al 2 O 3 51,52 …”
Section: Introductionmentioning
confidence: 99%
“…Although it is well-reported that certain cations, such as Ca 2+ , Zr 4+ , Fe 3+ , and Ti 4+ , accelerated structural changes, other cations like Ba 2+ , La 3+ , and Si 4+ delayed them. 43,49,50 Several groups have also suggested that the pH of starting Al(OH) 3 powder suspensions influenced the final particle size and shape, 30 which affected the onset temperature of α-Al 2 O 3 formation, as well as the transformation sequence leading to α-Al 2 O 3 . 51,52 Although significant progress has been made to understand the effect of sodium on properties of alumina, its influence on transformation of γ-Al 2 O 3 remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina ceramic cores are ceramic parts with especially fine and complex structures, serving as a medium for the formation of the internal structure of high‐temperature metallic hollow turbine blades, used in aircraft engines 7 , 8. Indeed, the characteristics of the alumina ceramic cores determine the precision and quality of the blades 9 .…”
Section: Introductionmentioning
confidence: 99%